Transforming businesses with bitcoin mining and blockchain applications - Rajput, Dharmendra Singh 1985-; Thakur, Ramjeevan Singh 1974-; Basha, Syed Muzamil 1986- (IGI Global, 2020)
"This book examines the use of bitcoin mining and blockchain applications in business"--